Review of Debates Surrounding the Role of the First Language in the Second Language Classroom (International Journal of Scientific Research in Science and Technology, 2025)
Nowaday, teaching and learning foreign language is unavoidable. Then, there are more and more argurments about the methods of studying and teaching it. Among them, should the first language or the target one be used in class is a question. Therefore this paper aims to summarize the use of the first language in the second language classroom in differents methods and two approachs toward it.
Keywords: use of L1 in L2 classroom; role of L1 in L2 classroom